Introdução ao estudo da álgebra no ensino fundamental - Pinheiro, Patricia Aparecida (2013)
This study is based on considerations regarding the teaching and learning of algebra in its introductory phase with seventh graders and eighth year of elementary school, having as final product an instructional sequence with the objective of introducing algebraic thinking more effectively. At first, there is a discussion of issues related to the introduction to the study of algebra, such as the difficulties and mistakes that students have upon the lights of the thoughts of various authors and researchers in Mathematics Education. It also provides general guidelines for teaching this subject according to official documents (Brazilian Curricular Parameters and Curricular Proposal of the State of São Paulo). Moreover, it contains a proposed instructional sequence that aims to introduce algebraic thinking effectively, bringing even discussions about the chosen methodologies. The second phase deals with the application of this sequence into two classes of eighth year of a public school from the state of São Paulo. Finally, we expose our impressions, the student outcomes and also suggestions in order to the sequence can be used and improved by other teachers.